Seismic Non-Limited Active Earth Pressure Analysis of Retaining Walls Under Rotation-About-the-Base Mode - Zhiliang Sun; Wei Wang (Applied Sciences)
Under seismic loading conditions, the backfill soil behind retaining walls does not fully reach the limit state, while seismic earth pressure is influenced by wall displacement. The RB (rotation about the base) displacement pattern represents a prevalent deformation mode in retaining walls during operational service. To calculate the seismic non-limited active earth pressure under RB mode, this study first establishes the relationship between critical horizontal displacement (corresponding to a fully mobilized wall–soil interface friction angle) and depth based on numerical simulations, revealing a linear correlation. Subsequently, nonlinear distribution relationships for the mobilized soil internal friction angle and wall–soil interface friction angle with wall-top displacement are derived. Building upon this foundation and considering the failure mechanism of backfill soil under RB displacement, the soil mass is divided into inclined slices. A pseudo-static analytical framework is proposed to calculate both the magnitude and application point of non-limited seismic earth pressure for rigid walls under RB displacement. Validation against experimental data from referenced studies demonstrates the method’s rationality. Earth pressure transitions from an initially concave triangular distribution to a linear pattern as displacement progresses. The application point descends from the initial at-rest position (1/3 H) with increasing wall-top displacement, subsequently rising as the soil approaches full active limit states, ultimately stabilizing at 1/3 H under linear pressure distribution. The parameter sensitivity analysis section summarizes that the horizontal seismic coefficient dominates influencing factors, followed by wall displacement, while soil internal friction angle and soil–wall interface friction angle exhibit relatively minor effects. These findings provide critical insights for optimizing seismic design methodologies of retaining structures.